Introducing the Cities of Ghazali in the Context of Religious Tourism - Demircioğlu, Aytekin (IGI Global, 2021)
Ghazali is one of the most well-known scholars of the Islamic world that lived between 1058 and 1111. He was dedicated to knowledge in his short life. Ghazali made trips to take lessons and to teach. In this study, cities related to Ghazali were examined. These cities are Tus, where he was born and received his primary education; Curcan, where received Fiqh training; Nishabur, where he first studied as a student and then taught as a madrasa scholar. These three cities are located within the borders of Iran today. The fourth city is Baghdad, where he taught at the Nizamiye Madrasa. Later he was found in the cities of Damascus, Jerusalem, Al-Halil, respectively. He then went to the cities of Mecca and Medina to become a pilgrim. In this study, these nine cities, which are important for Muslims, were introduced as a religious tourism center with a descriptive method.
Keywords: 4. Education; 11. Sustainability